Odpowiedź :
Odpowiedź:
zad.1- D
zad.2 - B
zad. 3- 2do potęgi 4 ; 4² ; 5² ; 3³
zad. 4 - A
zad.5- a) =5/6 b) = 11/4= 2 3/4 c) = 14·2·10= 280 d) =3·4·5= 60
zad. 6 - C
zad.7
a) = (7/4)² = 49/16 = 3 1/16
b) (- 7/5) ³ = - 343/125 = - 2 93/125
c) = (25/7)² = 625/49 = 12 37/49
d) = (7/3) ³ = 343/27 = 12 19/27
zad 8
a) = 3³ : 3 ( do potęgi 1) = 3² = 9
b) = 5 ( do potęgi 0 ) : 5 ( do potęgi 1) = 1/5
c) = 4 ( do potęgi 14 ) : 4 ( do potęgi 6) / 4 ( do potęgi 6) =
= 4 ( do potęgi 8) : 4 ( do potęgi 6) = 4² = 16
d) = 2 ( do potęgi 8) : 2 ( do potęgi 4) · 2 ( do potęgi 4) / 2 ( do potęgi 4) =
= 2 ( do potęgi 4) : 2 ( do potęgi 4) = 2 ( do potęgi 4) = 16
zad. 9
a) = √36 = 6
b) = √36 = 6
c) = √81 = 9
d) = √100= 10
e) = ∛8 = 2
f) = ∛0,064 = 0,4
g) = ∛0,216 = 0,6
h) = ∛0,001 = 0,1
zad.10
a) = √4 = 2
b) = √9 = 3
c) = √4 = 2
d) = √28 : √63 = [tex]\sqrt{4*7} \\[/tex] : [tex]\sqrt{9*7} \\[/tex] = 2√7 : 3√7 = 2/3
e) = ∛8 = 2
f) = ∛27 = 3
g) = ∛32 : ∛500 = [tex]\sqrt[3]{4*8} \\[/tex] : [tex]\sqrt[3]{4*125} \\[/tex] = 2 ∛4 : 5∛4 = 2/5
h) = [tex]\sqrt[3]{27*3} \\[/tex] : [tex]\sqrt[3]{64*3}[/tex] = 3∛3 : 4∛3 = 3/4
Szczegółowe wyjaśnienie: